1999
DOI: 10.1126/science.285.5424.73
|View full text |Cite
|
Sign up to set email alerts
|

Structural Rearrangements Underlying K + -Channel Activation Gating

Abstract: The intramembrane molecular events underlying activation gating in the Streptomyces K+ channel were investigated by site-directed spin-labeling methods and electron paramagnetic resonance spectroscopy. A comparison of the closed and open conformations of the channel revealed periodic changes in spin-label mobility and intersubunit spin-spin interaction consistent with rigid-body movements of the two transmembrane helices TM1 and TM2. These changes involve translations and counterclockwise rotations of both hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

50
481
1
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 539 publications
(535 citation statements)
references
References 27 publications
50
481
1
3
Order By: Relevance
“…quency 2.50 cm Ϫ1 . This mode revealed a totally concerted tilting and rotation of the transmembrane helices TM1 and TM2 (7)(8)(9)29). The motion of the TM1 helices is mainly a tilting and rotation around a hinge formed between Ser-44 on TM1 and Ser-69 on the small-pore helix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…quency 2.50 cm Ϫ1 . This mode revealed a totally concerted tilting and rotation of the transmembrane helices TM1 and TM2 (7)(8)(9)29). The motion of the TM1 helices is mainly a tilting and rotation around a hinge formed between Ser-44 on TM1 and Ser-69 on the small-pore helix.…”
Section: Resultsmentioning
confidence: 99%
“…This cavity is connected to the cytoplasm by a relatively long hydrophobic pore, which is also the location of the intracellular gate of KcsA. Electron paramagnetic resonance (EPR) measurements showed that the diameter of this hydrophobic pore increases when the pH is lowered (7)(8)(9). Minimal change in intersubunit distance near residues Thr-107 to Ala-108 also was observed (9), which led to the speculation that this region serves as a pivot point for the overall motions of the helices.…”
mentioning
confidence: 99%
“…(1) Upon a positive change in membrane potential S4 moves outward and rotates 180° (Keynes and Elinder 1999). (2) S6 rotates 15° and opens the activation gate (Perozo et al 1999). (3) Residue 451 rotates toward 418, and 450 is removed from its position in the aromatic cuff (Larsson and Elinder 2000).…”
Section: Tablementioning
confidence: 99%
“…The inner KcsA helices form an important part of the conduction pathway. Previous electron paramagnetic resonance experiments showed that they rotate upon activation in a counterclockwise direction, thereby opening the conduction pathway (15,16). Furthermore, solid-state NMR (ssNMR), which can be applied in lipid bilayers (17)(18)(19)(20), provided detailed insights into the structural basis of the coupling of KcsA activation and inactivation gates during channel gating (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%